A GUI-BASED DATA ACQUISITION SYSTEM FOR EIT USING TWO CURRENT INJECTION METHODS - Zarkasi, Ahmad; Hananda Putra, Muhammad Fauzan; Natalisanto, Adrianus Inu; Nurhanafi, Kholis; Hidayatullah, Muhammad; Kusmiran, Amirin; Nuraidha, Amalia C (Universitas Mataram, 2024)
The current injection method played an essential role in the data quality of impedance measurement using the electrical impedance tomography (EIT) technique. Previous studies have largely utilized only a single current injection method with limited interface access, which restricts the effectiveness of EIT systems. In this paper, a graphical user interface (GUI)-based data acquisition system was designed to improve user interaction and optimize the control system. The system was equipped with multiple current injection methods, allowing researchers to choose which method to use in the measurement process. The designed hardware comprises a V-to-I converter circuit, multiplexer, electrodes, peak detector, and filter circuit. Testing results indicate that the V to I converter circuit has an average peak difference between voltage and current of 4.86% and an average error of 0.69% in the peak detector circuit. The multiplexer circuit switches quickly and consistently, while the filter circuit remains stable at the 50 kHz frequency used in this study. These results demonstrate that the designed circuits perform adequately and effectively, ensuring reliable and accurate measurements. Â Additionally, the data acquisition software, presented as a GUI, effectively facilitates the selection of current injection methods and the display of boundary data simulation (BDS) on the object. This is demonstrated by the spatial inhomogeneity patterns visible through BDS in both the adjacent and opposite methods